Photoluminescence of ZnS Luminophore Sonofragmentated in Isopropyl Alcohol Solution - Zakirov, M.; Korotchenkov, O.; Rybak, Ya (Journal of Nano- and Electronic Physics, 2016)
The paper presents a new method of producing nanosized SiO2 particles by a sonochemical reaction in a mixture of SiC in distilled water. FTIR spectra exhibit absorption peaks characteristic of different modes of oscillation in the amorphous SiOx. Optical transmittance spectra demonstrate three characteristics components with energies of 2.9, 3.6 and 4.1 eV, which correspond to non-bridging oxygen hole center and ≡Si-O-O•;band at 3.6 eV associated to chain ≡Si–O–O–Si≡ and point defects in dicoordinated silicon lone pair, ≡Si–O–Si–O–Si≡, respectively.